Controllable polarization of lasing emission from a polymer microfiber laser - Ta, Van Duong (2020)
Microlasers with controllable polarization of output emission are vital for on-chip optical communications, optical sensors and optical switches. In this work, we report a high quality (Q) factor, low-threshold polymer microfiber laser and the possibility of achieving laser emission with a desired polarization. The microfiber is fabricated by direct drawing from a dye-doped polymer solution and it can generate whispering gallery mode (WGM) lasing under optical pulse excitation. When the microfiber is pumped from the side with pumping direction perpendicular to the microfiber's axis, the polarization direction of the output laser is found to be the same as that of the pump laser. Lasing emission with either transverse electric (TE) or transverse magnetic (TM) modes can be obtained and these two polarization states can be switched over by tuning the pumping laser. Furthermore, emission with both TE and TM modes can also be observed by changing the orientation of the microfiber relatively to pumping direction. Our finding provides an effective approach for achieving microlasers that have high Q lasing modes with anticipated polarization.